Intention of pursuing nursing as a career and its associated factors among male students in the schools of Banepa Municipality, Nepal - Shrestha, Sulekha; Sharma, Alisha (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Nepal Nursing Council issued a notice regarding the inclusion of men in nursing in June 2018. Even with this mandate, only a handful of male students claimed the reservation for nursing education. This study aimed to determine the intention of pursuing nursing as a career and its associated factors among male students in the schools of Banepa Municipality, Kavre, Nepal.Method: A quantitative analytical cross-sectional research design was adopted and data was collected via convenience sampling technique. A semi-structured questionnaire was administered among male students of grade 10 of the selected schools.Result: Among 190 respondents, only 11.8% had an intention to pursue the nursing profession as a career. Global opportunities, challenging careers, and reasonable pay were apparent factors that influenced students. However, lack of social support, lack of role model, disrespect, and unpleasant work environment was the major inhibiting factors. Furthermore, the intention to pursue nursing as a career was significantly common among the male students who were acquainted with a nurse and had exposure to nursing care.Conclusion: The majority of the participants had a positive perception of nursing but did not prefer to pursue nursing as a career due to lack of social support, lack of role models, disrespect, and an unpleasant work environment.